A decentralised linear programming approach to energy–efficient event detection. (1st January 2015) - Yuan, Kun; Ling, Qing; Tian, Zhi
This paper addresses the problem of decentralised event detection in a large–scale wireless sensor network (WSN), where without the coordination of any fusion centre, sensor nodes autonomously make decisions through information exchange with their neighbours. We formulate the event detection problem as a linear program, and propose a heuristic decentralised linear programming (DLP) approach to solve it. Compared to the existing algorithms which solve decentralised optimisation problems, the DLP algorithm requires low communication cost per iteration and shows fast convergence. Convergence property of the DLP algorithm is theoretically analysed, and then validated through simulation results. We also implement the DLP algorithm in the structural health monitoring application and demonstrate its effectiveness in decentralised event detection.